Tanggung Jawab Hukum atas Penyalahgunaan Teknologi AI: Studi Kasus Deepfake Prabowo Subianto dalam Modus Bantuan Uang: Legal Liability for the Misuse of AI Technology: The Case of the Prabowo Subianto Deepfake in a Money-Laundering Scheme - Sofia; Rina Shahriyani Shahrullah; Ampuan Situmeang (Faculty of Law Hang Tuah University, 2026)
The development of deepfake artificial intelligence technology poses new challenges for Indonesian criminal law because it can be used to digitally manipulate a person’s face, voice, and identity. This study aims to analyze the modus operandi of deepfake AI technology abuse as well as the legal liability of perpetrators in digital fraud crimes. This study employs a normative legal research method using a statutory approach, a case-based approach, and a conceptual approach. The results indicate that the modus operandi of deepfake misuse involves the dissemination of AI-generated manipulative videos featuring President Prabowo Subianto, purporting to offer financial assistance to the public, accompanied by a WhatsApp number to direct victims to communicate with the perpetrator and transfer funds. Legal liability in this case arises because the perpetrator’s actions satisfy the elements of a criminal offense: there is intent, the perpetrator possesses the capacity to be held accountable, and no justifying or exculpatory grounds are found. This criminal liability is based on Article 51(1) in conjunction with Article 35 of the ITE Law and Article 378 of the Criminal Code, while the PDP Law is used as a supporting normative instrument in addressing the misuse of digital identities in the form of faces and voices. This study underscores the importance of strengthening regulations, digital evidence, and harmonizing legal frameworks regarding the misuse of deepfake technology.